2 - Les contre-performances de l'agro-industrie ivoirienne : un essai de justification par l'ap- proche structuraliste du paradigme structure- comportement-performance (SCP): par René N'Guettia Kouassi - Kouassi, René N'Guettia (Africa Development, 2001)
This study analyses the performance of the agriculture-based industry in Côte d'Ivoire through the framework of its market structure. Though it underlines the importance of the modern approach to such a problem, it confines itself to thetheoretical framework of the traditional approach to industrial organization. The analyses show that the economic efficiency of the agriculture-based industry is a paradoxical situation due to protectionism and lack of diversity. It argues that the advantages accruing from the structure of the industry have not been sufficient enough to impact on the food economy of the country. The reasons for this inadequacy are twofold: The sectors of the industry with relative performance are controlled by private interests and are particularly dominant in sectors not well connected to the local agriculture. Secondly, the influence of the state in sectors controlled by national interests impedes their performance because it allows some practices (wastage, embezzlement of public funds, etc.) which are opposed to the virtues of the rational management of the economy which would in turn, find its roots in community constraints in Africa.